Building of EMR Tools to Support Quality and Research in a Memory Disorders Clinic - Simon, Kelly Claire; Yucus, Chad; Castle, James; Chesis, Richard; Lai, Rebekah; Hillman, Laura; Tideman, Samuel; Garduno, Lisette; Meyers, Steven; Frigerio, Roberta; Maraganore, Demetrius M. (Frontiers in Neurology, 2019)
The electronic medical record (EMR) presents an opportunity to standardize patient data collection based on quality guidelines and conduct practice-based research. We describe the development of a customized EMR “toolkit” that standardizes patient data collection with hundreds of discrete fields that supports Best Practices for treating patients with memory disorders. The toolkit also supports practice-based research. We describe the design and successful implementation of a customized EMR toolkit to support Best Practices in the care of patients with memory disorders. We discuss applications, including quality improvement projects and current research initiatives, using the toolkit. This toolkit is being shared with other departments of Neurology as part of the Neurology Practice-Based Research Network. Data collection is ongoing, including longitudinal follow-up. This toolkit will generate data that will allow for descriptive and hypothesis driven research as well-quality improvement among patients seen in a memory clinic.